Vibrio parahaemolyticus flagellin induces cytokines expression via toll-like receptor 5 pathway in orange-spotted grouper, Epinephelus coioides. Issue 87 (April 2019) - He, Liangge; Liang, Yaosi; Yu, Xue; Peng, Wan; He, Jianan; Fu, Lijun; Lin, Haoran; Zhang, Yong; Lu, Danqi
Abstract: Vibrio parahaemolyticus is the major pathogen of vibriosis in aquatic animals and causes inflammation that may be related to tissue damage. Here, we have established a V. parahaemolyticus flagellin stimulation model using grouper spleen (GS) cell line. Purified V. parahaemolyticus flagellin was used to stimulate GS cells. Our results showed that the mRNA levels of orange-spotted grouper ( Epinephelus coioides ) toll-like receptor 5M ( Ec TLR5M), Ec TLR5S and downstream cytokines, such as interferon-γ2 (IFN-γ2), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), were all significantly increased after stimulation with V. parahaemolyticus flagellin in GS cells. Gene silencing of the Ec TLR5M and Ec TLR5S in GS cells by using small interfering RNA resulted in suppression of the V. parahaemolyticus flagellin-induced cytokines expression. We further demonstrated that activation of both mitogen-activated protein kinases (MAPKs) and nuclear factor-kappa B (NF-κB) were required for cytokines expression. We observed that the phosphorylation of NF-κB inhibitor-α (IκBα), extracellular signal-regulated kinase (ERK) and p38 were induced following treatment with flagellin. Additionally, most of p65, a NF-κB subunit, was found to translocate to the nucleus after 60 min stimulation. Overall, our results suggest that V. parahaemolyticus flagellin influences cytokines expression, such as IFN-γ2, IL-6 and TNF-α, via Ec TLR5s recognition and MAPKs/NF-κB signaling pathway activation in GS cells. Highlights: V. parahaemolyticus flagellin induced IFN-γ2, IL-6 and TNF-α mRNA expressions. V. parahaemolyticus flagellin induced MAPKs and NF-κB pathways activation in GS cell. Gene silencing of the Ec TLR5s suppressed flagellin-induced cytokines expression.